The USER Study: A Chart Review of Patients Receiving a 0.2 µg/day Fluocinolone Acetonide Implant for Diabetic Macular Edema - Alexander Eaton; Sean S. Koh; Jaime Jimenez; Christopher D. Riemann (Ophthalmology and Therapy, 2018)
Abstract Introduction To determine anatomical, functional, and intraocular pressure (IOP) responses to diabetic macular edema (DME) treatments pre- and post-0.2 µg/day fluocinolone acetonide (FAc) implant administration compared with baseline and the preceding 3 years. Methods This was a retrospective, chart review, cohort study in four U.S. centers. Patients received the 0.2 µg/day FAc implant for the treatment of DME in at least one eye before January 1, 2016. DME treatments administered up to 36 months pre-FAc implant and up to 24 months post-FAc implant were recorded, and treatment frequency was calculated. Visual acuity (VA) was assessed using a Snellen eye chart and converted to early treatment diabetic retinopathy study (ETDRS) letters, and central subfield thickness (CST) was measured using optical coherence tomography (OCT). Treatment frequency, mean VA, mean CST, percentage of patients with CST of ≤ 300 µm, mean IOP, IOP events, and IOP treatments pre- and post-FAc implant administration were measured. Positive and negative predictive values for the IOP response to prior steroid therapy were also determined. Results In total, 160 eyes of 130 patients were studied. VA was maintained at pre-FAc levels from baseline to month 24, despite a significant reduction in treatment frequency from one treatment every 2.9 months pre-FAc implant to one treatment every 14.3 months post-FAc implant. Patients with better baseline VA required fewer DME treatments post-FAc than did patients with worse baseline VA. The majority of patients did not require additional DME treatment during the post-FAc follow-up period. A significant reduction in CST and an increase in the percentage of patients with CST of ≤ 300 µm were seen up to month 21 post-FAc implant. Pre-FAc implant IOP was maintained during the post-FAc implant period; increased IOP with prior steroid therapy was found to be highly predictive of increased IOP post-FAc implant. Conclusion The results of this study confirm the positive safety and efficacy profile of the FAc implant and demonstrate for the first time the effectiveness of the U.S. label indication of FAc in reducing the incidence of post-treatment pressure elevation. The FAc implant significantly reduced treatment burden in the overall population without significantly increasing the risk of steroid-induced pressure elevation. Funding Alimera Sciences.